Georgina Beier in Papua Neuguinea (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Photographs; Women; Artists; Women artists; Papua New Guinea; New Guinea